KAJIAN STABILITAS SISTEM KELISTRIKAN INDUSTRI - Dulhadi Dulhadi; Dewi Indriati Hadi Putri (KURVATEK, 2020)
This research discusses the dynamic behavior of the operation of several synchronous generators in industrial electrical systems and to find out various factors that affect the stability of the electric power system. This research aims to develop an analysis method of stability that is practical, informative, and quite accurate. The analysis was performed by step by step numerical integration method. Observations were made on the oscillations between rotors, the simultaneity of the generator, the ability and speed of the system to reach a new steady state.The results of this research indicate that electrical system disturbance can cause oscillations between generators which reduce the ability and speed of the system in achieving steady-state conditions. This oscillation creates voltage and frequency fluctuations for a long time. Stability margins can be increased by regulating the burden for each generating unit corresponding with the characteristics and capabilities of each generator, network configuration, and operating load. Simulations of several cases indicate that the generator response to electrical noise very influenced by operating conditions, clearing time, location of disturbance, and changes in network configuration.Keywords: Transient stability, multi-machine system, step by step integration